Pre–Post Evaluation of a Rural Indonesian Posbindu Cadre-Led Health Promotion Program on Cardiovascular Knowledge, Physical Health, and Mental Well-Being - Pramitha Esha Nirmala Dewi; Sri Tasminatun; Nanang Kurniawan; Hikma Yulia Putri; Githa Fungie Galistiani; Imania Afidatus Syaifabila; Muhammad Thesa Ghozali (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: This study aimed to evaluate the impact of a cadre-led intervention on physical health, cardiovascular knowledge, and mental well-being in rural Indonesian communities. Cardiovascular disease remains a leading cause of mortality in Indonesia, particularly in rural areas with limited healthcare access and low health literacy. With a growing burden of non-communicable diseases in low-resource settings, the objective was to assess a community-based approach addressing early detection and lifestyle modification gaps in the existing literature. Methods: This quasi-experimental one-group pre-post study was conducted over six weeks in a rural Indonesian setting. A total of 91 adult participants were enrolled, and data were collected through anthropometric measurements, biochemical tests, a 15-item cardiovascular knowledge questionnaire, and the Patient Health Questionnaire-9 (PHQ-9) for mental health screening. Ethical approval was obtained from the Medical and Health Research Ethics Committee of the Faculty of Medicine and Health Sciences, Universitas Muhammadiyah Yogyakarta, Indonesia. Results: The primary outcome of the study was the change in cardiovascular risk indicators and knowledge. Findings showed a significant reduction in BMI (mean change = -0.56 kg/m², 95% CI: -0.83 to -0.29, p < 0.001, Cohen’s d = 0.47) and waist circumference (mean change = -0.91 cm, 95% CI: -1.80 to -0.02, p = 0.044, Cohen’s d = 0.28), along with a significant improvement in cardiovascular knowledge scores (mean change = +9.00, 95% CI: +3.44 to +14.56, p = 0.002, Cohen’s d = 0.68). Additionally, PHQ-9 screening showed that 76.9% of participants reported minimal depressive symptoms at the time of assessment. Statistical analyses indicated the effectiveness of the intervention in improving physical and knowledge-related health outcomes. Conclusion: This study contributes to the understanding of health promotion in low-resource rural settings by demonstrating the effectiveness of cadre-led interventions for cardiovascular contexts and the feasibility of integrating mental health screening into community programs. Future studies should explore long-term sustainability and scalability, advancing knowledge in the field of international health.